Islam in contemporary Malaysia: rules pertaining to comparison of narrations with established historical facts according to Ibn Al-Qayyim - Muhamad Rozaimi Ramle,; Sahul Hamid Mohamad Maideen, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Islam is the official religion of Malaysia and is practised by some 60 per cent of its population. As such it is not surprising that the proper study of Islam is organic in the everyday life of Malaysian Muslims. One area of ardent concern is the process of evaluating Hadith in particular, the stringent efforts undertaken by the Islamic scholars in order to ensure the authenticity of narrations. Various parameters were adopted to execute the task. One of the most significant methods used to preserve the authenticity was by making comparison and testing it with established historical facts. In this case, Ibn al-Qayyim was a prominent scholar to apply such method in his magnificent book Zad al-Ma’ad. This study took a closer look at the Ibn al-Qayyim’s approach using the aforementioned method to evaluate the narrations of al-Maghazi and al-Siyar. It mainly utilised Zad al-Macad as the principal source in order to examine the contents pertaining to the comparison of narrations and historical facts. The findings revealed that there were various methods applied by Ibn Al-Qayyim in confirming historical events, namely, referring to the consensus of the scholars of battles and biographies, using their silence as evidence, and considering the continuation of acting upon the essence of the narration at the time of the Rightly Guided Caliphs.